(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the historical and philosophical dimensions of the relationship between human beings and the natural environment, focusing particularly on the ethical foundations that underpin sustainable development. Drawing on ancient sources such as the Avesta and traditional mystical worldviews, the paper investigates how ecological ethics has been expressed in spiritual and moral heritage throughout different civilizations. The study emphasizes that sustainable development requires not only technological and economic solutions but also a rethinking of humanity’s moral responsibility towards nature. The article further discusses the interrelation between ecological awareness and the principles of the green economy, arguing that a value-based approach rooted in ethical norms is essential for building a more harmonious and sustainable future.